2019
DOI: 10.1088/1742-6596/1246/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Pre and intraoperative findings of chronic otitis media

Abstract: Chronic otitis media (COM) is still highly prevalent in developing countries and often become main cause of deafness and morbid complication. Appropriate management may decrease the morbidity and mortality rate. The aim of the study are to evaluate preoperative and intraoperative finding among COM patients. A descriptive study was conducted at Mohammad Hoesin Hospital Palembang from April 2015 to April 2018. A secondary data was taken from medical records. A total of 252 patients were included in this study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…These results were in line with previous research conducted by Irwan et al. 9 at Dr. Mohammad Hoesin Hospital, Palembang, that out of the 252 CSOM patients, most had mastoiditis with cholesteatoma (62.69%) and 14.28% with sclerotic lesions. The most common HL found in that study were conductive HL (49.98%), followed by sensorineural HL (6.34%).…”
Section: Discussionsupporting
confidence: 92%
“…These results were in line with previous research conducted by Irwan et al. 9 at Dr. Mohammad Hoesin Hospital, Palembang, that out of the 252 CSOM patients, most had mastoiditis with cholesteatoma (62.69%) and 14.28% with sclerotic lesions. The most common HL found in that study were conductive HL (49.98%), followed by sensorineural HL (6.34%).…”
Section: Discussionsupporting
confidence: 92%
“…There are more safe type CSOM patients than hazard type CSOM with a percentage of 55.6%. Cholesteatoma is a cystic lesion formed by abnormal accumulation of keratinized squamous epithelium in the middle ear, epitympanum, mastoid cavity, petrous apex, or temporal bone [15].…”
Section: Discussionmentioning
confidence: 99%
“…The bluestone classification further classifies cholesteatoma based on its location and invasion [16,17]. Classification consists of: Stage 1: cholesteatoma confined to the middle ear (hypoepitympanum and mesoepitympanum), without erosion of the ossicular chain; Stage 2: stage 1 with erosion of one or more ossicles; Stage 3: involves the middle ear and mastoid gas cell system without erosion of the auditory ossicles; Stage 4: same as stage 3 but with erosion of one or more ossicles; Stage 5: extensive cholesteatoma of the middle ear, mastoid, and other parts of the temporal bone, whose extent is not fully accessible for surgery (eg, medial to the labyrinth), with one or more ossicles involved with or without a labyrinthine fistula; Stage 6 is the same as stage 5, but the cholesteatoma extends beyond the temporal bone [15,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a study that found that of the 279 ears of patients with CSOM, erosion of the hearing bones was more common in CSOM with cholesteatoma (69.3%) than in CSOM without cholesteatoma (13.9%). [10][11][12][13][14] More than twothirds of CSOM patients with cholesteatoma have an ossicular discontinuity. Another study stated that discontinuity of the ossicles was found in 87.5% of patients with cholesteatoma.…”
Section: Correlationmentioning
confidence: 99%